Construction of a water resource suitability index for agricultural production and matching analysis of cultivated land in Lhasa, Tibet - Liu, Yumei; Wang, Zhiyong; Wang, Chuansheng; Wang, Yafei; Li, Jiuyi; Liang, Liqiao (Frontiers in Environmental Science, 2023)
Water resources are essential for agriculture. In the spatial layout of agricultural production, quantitatively identifying the spatial differences in water resource conditions, including precipitation and irrigation water supply factors, is necessary. Here, a water resource suitability index for agricultural production (WRSIA) was constructed for agricultural development using irrigation water supply convenience (IWSC) and precipitation conditions. Considering Lhasa as the study area, WRSIA was calculated on a 100 m grid scale, and the spatial distribution relationship between WRSIA and cultivated land was analyzed using geographically weighted regression (GWR). The results showed that IWSC severely restricted agricultural production in Lhasa, and the high WRSIA values were mainly distributed in the valleys of the Lhasa River and its tributaries. Moreover, 47.7% of the cultivated land was distributed in 5% of the area having the highest water resource suitability. According to GWR, the cultivated land area and water resource availability were strongly correlated (R2= 0.904). The distribution of the cultivated land was well explained by WRSIA, which could describe the differences in water resource suitability for agricultural production. Furthermore, the suitability of agricultural production was better evaluated when WRSIA was coupled with the land resource suitability index. Overall, WRSIA showed high applicability in Lhasa and other regions, thereby providing a scientific basis and technical support for the spatial layout of agricultural production.